Educommunication: pedagogical intervention strategy in adolescents with motor, cognitive and unplanned impulsivity - Álvarez Idarraga, Nelly Johana; Suarez Mira, Gustavo Adolfo (Rastros Rostros, 2023)
The objective of this article is to highlight the feasibility of the use of educommunication in the reflection of impulsive cognitive, motor, and unplanned behaviors. What is revealed is the result of a pedagogical intervention that sought to design an educommunicative program through Problem-Based Learning. The selected methodology is a sequential explanatory study, developed through a mixed approach and a descriptive method. As a result of the analysis, effectiveness in behavioral reflection and appropriation of the educommunicative strategies exposed in the investigative spaces that involved the interests, social realities, and tangible affections of the students is manifested. It is concluded that the use of educommunication promotes self-regulation, favors the development of social skills, and encourages assertive decision-making.